Learning Styles against Students Understanding Mathematical Concepts - Mazroatul Ulum; Heni Pujiastuti (Universitas Jambi, 2020)
Student has a different level of understanding of mathematical concepts, such as they may prefer graphics, printed words, listening or using experiences and practices in representing information. This is driven by several factors, one of which is the learning style. This study aims to determine the effect of the learning styles possessed by students on the level of students' understanding of mathematical concepts. The learning style used in this study is a learning style with individual modalities (the use of sight, hearing, and movement senses). This research is a qualitative descriptive study with research subjects, namely 8 students of class VIII SMP who come from the same school and class. The data collection instruments used in this study were non-test and test instruments. The non-test instrument was a VAK learning style questionnaire with 10 statements and the test instrument used was 7 descriptive questions with the subject of flat-sided space shapes. Questionnaire data processing and understanding of mathematical concepts are carried out using the percentage formula. Advanced data processing for understanding students' mathematical concepts, by categorizing, then analyzing data and drawing conclusions. From the results of this study the conclusion obtained  there was no significant effect of the learning styles possessed by students on the level of students' ability to understand mathematical concepts.